LITTER DECOMPOSITION IN Rhizophora sp. MANGROVE STANDS OF VARYING PLANTING AGES - Kadarsah, Anang (The Journal is published by Graduate Programe of Lambung Mangkurat University, 2016)
Information about litter decomposition in Rhizophora Sp. mangrove stands of different planting ages is very important to find out the main factors affecting the whole information on structure and function of mangrove ecosystem and to improve mangrove management in the future. The objective of this study was to determine the litter decomposition in Rhizophora sp. mangrove stands of varying planting ages, with a case study in Subang Regency, West Java Province. Comparisons of litter decomposition were taken from five stands of planting ages (4 years, 12 years, 21 years, 29 years, and 38 years old). Four parameters of litter decomposition compared were dry weight of litter, decomposition rate, litter decomposition coefficient, and half-life time. The observation on Rhizophora Sp. mangrove stands was conducted in three plots of 10 m x 10 m. The results show that the litter decomposition parameters, especially dry weight of litter, decomposition rate, litter decomposition coefficient, and half-life time, were different on each planting age of Rhizophora sp. mangrove stands. The fastest time for litter decomposition was found in 12 years old of Rhizophora Sp. stands with the achievement for 90 days of observation and the decomposition efficiency of 100%. Meanwhile, the slowest was found in 38 years old of Rhizophora Sp. mangrove stands with more than 120 days, and the litter decomposition efficiency was about 97.84%. Environmental conditions (soil and water conditions, nitrogen content, and soil fauna) play a major role on its differentiation. It can be concluded that the litter decomposition in Rhizophora sp. mangrove stands of varying planting ages change over time because of the environmental conditions, but the complexity of the relation between ages is not always apparent.